Synthesis, antimicrobial activities of novel 3-chloro-4-(2, 4-difluorophenyl)-1-(3-aryl-1, 8-naphthyridin-2-yl)azetidin-2-ones and 2-(2, 4-difluorophenyl)-3-(3-aryl-1, 8-naphthyridin-2-yl)thiazolidin-4-ones. Issue 5 (4th March 2022) - Adem, Kurumanna; Boda, Sakram; Sirgamalla, Rambabu; Macha, Ramesh
Abstract: A novel series of 3-chloro-4-(2, 4-difluorophenyl)-1-(3-aryl-1, 8-naphthyridin-2-yl)azetidin-2-one 6(a–g) and 2-(2, 4-difluorophenyl)-3-(3-aryl-1, 8-naphthyridin-2-yl)thiazolidin-4-ones 7(a–g) were synthesized through the reaction of Schiff base 1-(2, 4-difluorophenyl)- N -(3-aryl-1, 8-napthridine-2-yl)methanimines 5(a–g) with chloro acetyl chloride and mercaptoacetic acid respectively. The chemical structures of the synthesized derivatives were established by 1 H-NMR, 13 C-NMR, mass spectral, and C, H, N analysis. The synthesized compounds were evaluated for antibacterial Staphylococcus aureus, Bacillus subtilis (two Gram positive) and Escherichia coli, Klebsiella pneumonia (two Gram negative) and antifungal Aspergillus flavus, Fusarium oxysporum . The synthesized compounds showed considerable activity of antibacterial and antifungal activity comparable to that of the reference drug. The molecular docking study was succeeded to identify the likely interactions with the new synthesized derivatives 6(a–g) and 7(a–g). Docking investigation confirmed that active molecule 6b, 6d, 6f and 7b, 7d, 7f have better docking scores with protein. Graphical Abstract: UF0001